2015
DOI: 10.1016/j.sbsr.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-chip system combining a microfluidic-ELISA with an array of amorphous silicon photosensors for the detection of celiac disease epitopes

Abstract: This work presents a lab-on-chip system, which combines a glass-polydimethilsiloxane microfluidic network and an array of amorphous silicon photosensors for the diagnosis and follow-up of Celiac disease. The microfluidic chip implements an on-chip enzyme-linked immunosorbent assay (ELISA), relying on a sandwich immunoassay between antibodies against gliadin peptides (GPs) and a secondary antibody marked with horseradish peroxi- dase (Ig-HRP). This enzyme catalyzes a chemiluminescent reaction, whose light inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In previous works [ 18 , 19 ], we have found that the photocurrents induced in a single junction a-Si:H photosensors by actual chemi/bio-luminescent signals are in the order of few-tens of pA. Therefore, the value of 2.5 pA chosen in our experiment represents a signal induced by a number of molecules very close to be realistically detected in a lab-on-chip application.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous works [ 18 , 19 ], we have found that the photocurrents induced in a single junction a-Si:H photosensors by actual chemi/bio-luminescent signals are in the order of few-tens of pA. Therefore, the value of 2.5 pA chosen in our experiment represents a signal induced by a number of molecules very close to be realistically detected in a lab-on-chip application.…”
Section: Resultsmentioning
confidence: 85%
“…To minimize the electromagnetic noise the measurements were performed in a Faraday cage. In practical LoC applications, the reduction of noise can be attained including the system in a small metal case as the one reported in [ 18 ].…”
Section: Device Characterizationmentioning
confidence: 99%
“…Meanwhile, the development of microfluidic technology is making tremendous progress. For example, the protein chips made of polydimethylsiloxane (PDMS) integrate micropumps, micromixers, and microvalves to manipulate fluids for the automatic concentration determination of the target protein [20][21][22][23][24]. However, the design of such microfluidic chips usually involves complicated chip design and manufacture, and fluid control is a highly complex process.…”
Section: Introductionmentioning
confidence: 99%
“…3 These drawbacks of the conventional immunoassay platforms are attributed to the prolonged incubation steps, which are due to the inefficient mass transport imposed by slow and infrequent delivery of antibody molecules to analytes immobilized on the solid matrix surface. 4,5 Leveraging microuidic principles for delivering reagents to the immunoreaction sites has alleviated this issue by considerably reducing the diffusion distances and allowing constant replenishment of the antibody molecules at the reaction site. [6][7][8] The additional utility of the microuidic immunoassays was to reduce the reagent volumes consumed, to incorporate multiple processes in a single device, and to signicantly lower overall analysis time.…”
Section: Introductionmentioning
confidence: 99%